Por uma escrita do corpo: representações "queer" na ficção de Al Berto - Martines, André Luiz Russignoli (Universidade Federal de São Carlos, 2018)
The literary production of the Portuguese writer Al Berto (1948-1997) can be understood not as, exclusively, the expression of a "homosexual" voice in the most recent Portuguese literature; it is, before that, a mode of representation - which a high aesthetic and historical value - of discourses that are transgressors of normativities that, historically, affect the body, gender and sexuality. This research aims to point out, from post-structuralist reflections, to what extent part of Al Berto's fiction can be considered a "writing of the body". The "Lunario" novel, published in 1988, is used as the main "corpus" for this analysis. Corporeity can be observed as a structuring element of Albertian fictional production. Conceptual categories such as "body", "homoeroticism" and "transgenderty" can therefore be understood under the theoretical perspective of queer studies, in order to problematize and point out part of Al Berto's fiction as a "writing of the body", in which, despite any normative or identity framing, desire and subjectivity legitimately assert themselves.
For a writing of the body: queer representations in Al Berto's fiction
Keywords: Teoria queer; Escrita do corpo; Ficção portuguesa; Al Berto; Queer theory; Writing of the body; Portuguese fiction; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS; LINGUISTICA, LETRAS E ARTES::LETRAS::TEORIA LITERARIA